Behavioral Economics and Islamic Consumption Values: A Conceptual Study on The Rojali-Rohana Phenomenon - Adhi Nur Muhammad; Lilik Rahmawati; Siti Musfiqoh (Niqosiya: Journal of Economics and Business Research, 2026)
Introduction: This study examines how prospect theory and Islamic consumption values intersect in explaining the rise of Rojali and Rohana in Indonesia. Research Method: Using a qualitative approach with a conceptual comparative design, the study analyzes secondary sources, including academic literature, consumer survey reports, and Islamic economic texts, through content analysis to identify points of convergence between the two frameworks. Results: The analysis shows a clear shift in the reference point of these consumers from seeking shopping satisfaction toward safeguarding financial stability, supported by stronger loss aversion and a growing tendency to delay gratification. Islamic values such as halal, tayyib, i’tidal, and the prohibitions of israf and tabdzir reinforce moral discipline that keeps consumption proportional. These psychological and ethical forces combine to create a cautious consumer profile where browsing, comparing prices, or leaving stores without purchasing reflects deliberate risk management rather than irrational hesitation. Their behavior protects financial well-being and aligns each purchase with religious and practical considerations. Conclusion: The main limitation of this study lies in its reliance on secondary data, which cannot fully capture lived consumer dynamics. Future research should adopt quantitative models to measure the scale of this phenomenon or employ ethnography and netnography for a deeper cultural examination of how this behavior emerges and evolves in everyday consumption.